Pronunciation Problems and Factors Affecting English Pronunciation of EFL Students - et. al., Teeraporn Plailek, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A good pronunciation is the foundation of effective spoken communication. If the speakers have unacceptable pronunciation, their utterances will not be comprehensible to listeners and as a result they will not be successful in their communication. The purposes of this study were to investigate the EFL students’ English pronunciation problems and to find out the factors affecting their English pronunciation. The participants were 208 students that use English as a foreign language in the Faculty of Education, Suan Sunandha Rajabhat University. The research instruments applied for data collection were an English pronunciation test, a questionnaire, and a semi-structured interview. The data obtained was analyzed by the applications of percentage, mean, standard deviation and content analysis. The finding revealed that English phonemes at the initial syllable position that create trouble to students included the /ð/, /θ/, /dʒ/, /ʒ/, /v/ and /z/ sound respectively and the /ð/, /θ/, /v/, /f/, /s/, and /l/ sound at the final syllable position. According to this study, the strongest factor that contributes t